Crystal structure of the high‐P polymorph of Ca2B6O6(OH)10·2(H2O) (meyerhofferite). Issue 6 (10th November 2021) - Comboni, Davide; Poreba, Tomasz; Pagliaro, Francesco; Battiston, Tommaso; Lotti, Paolo; Gatta, Giacomo Diego; Garbarino, Gaston; Hanfland, Michael
Abstract : Meyerhofferite is known to undergo a pressure‐mediated phase transition between 3.0 and 3.5 GPa. In this study, the crystal structure of the high‐pressure polymorph of meyerhofferite and its pressure‐induced deformation mechanisms are revealed, providing information aimed at improving knowledge of the high‐pressure phase transitions in this class of hydrated borates. Abstract : The crystal structure of the high‐pressure polymorph of meyerhofferite, ideally Ca2 B6 O6 (OH)10 ·2(H2 O), has been determined by means of single‐crystal synchrotron X‐ray diffraction data. Meyerhofferite undergoes a first‐order isosymmetric phase transition to meyerhofferite‐II, bracketed between 3.15 and 3.75 GPa, with a large volume discontinuity. The phase transition is marked by an increase in the coordination number of the boron B1 site, from III to IV, leading to a more interconnected and less compressible structure. The main structural differences between the two polymorphs and the P ‐induced deformation mechanisms at the atomic scale are discussed.